The best of intentions - Mason, Susan Anne (Mason, Susan Anne. Canadian crossings, 2018)
When Grace Abernathy's sister is rejected by the Easton family because of her low social class, Grace uses an assumed name to take on a position as nanny for her nephew Christian to see to his well-being, and soon ends up falling for the boy's guardian.